1980
DOI: 10.1111/j.1471-4159.1980.tb07092.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Alterations of Endoneurial Cholesterol and Fatty Acid in Wallerian Degeneration and Regeneration

Abstract: The endoneurial nonpolar lipids were serially examined throughout Wallerian degeneration and regeneration. Following nerve crush in the rat, the endoneurial content of cholesterol falls and cholesteryl ester content rises dramatically. The maximal alteration of this ratio corresponds reasonably well with events of myelin ovoid dissolution to sudanophilic amorphous lipids. Thereafter, as regenerative events overshadow degenerative events the ratio is slowly restored toward normal. The increased cholesteryl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…The cholesterol stores of these myelinating cells presumably had been used to synthesize the myelin that now enveloped the axons. This is in agreement with biochemical measurements that show that cholesteryl esters in the injured nerve decline after the second and third weeks (39). The cho-~~~~~~~~~~~~~~~~~.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The cholesterol stores of these myelinating cells presumably had been used to synthesize the myelin that now enveloped the axons. This is in agreement with biochemical measurements that show that cholesteryl esters in the injured nerve decline after the second and third weeks (39). The cho-~~~~~~~~~~~~~~~~~.…”
Section: Resultssupporting
confidence: 90%
“…Our data now show that these cholesteryl esters are depleted first in Schwann cells and then in macrophages and neurolemmal fibroblasts. Previous lipid analyses had shown that much of the free cholesterol originally in degenerating myelin is never stored as cholesteryl esters; high levels of free cholesterol persist in the injured nerve (39). Our study demonstrates that myelin degradation is completed as new myelin forms.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations